2015
DOI: 10.1007/s00381-015-2919-8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric gliosarcoma treated with adjuvant radiotherapy and temozolomide

Abstract: Adjuvant radiotherapy and temozolomide is well tolerated and show an encouraging survival in pPGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…They showed that temozolamide is well tolerated by pediatric patients and survival data with temozolamide therapy was encouraging. The two-year progression free and overall survival rates were 44.2 and 62.9%, respectively [27].…”
Section: Discussionmentioning
confidence: 98%
“…They showed that temozolamide is well tolerated by pediatric patients and survival data with temozolamide therapy was encouraging. The two-year progression free and overall survival rates were 44.2 and 62.9%, respectively [27].…”
Section: Discussionmentioning
confidence: 98%
“…During childhood, pineal tumors are more common, corresponding to 3%-11% of all pediatric central nervous system tumors. However, only 25 cases of pediatric nonpineal gliosarcoma had been reported, none of them in pineal topography [4] , [5] .…”
Section: Discussionmentioning
confidence: 99%
“…A literature review by Mallick et al. found a total of 25 reported cases of nonpineal pediatric gliosarcoma [4] .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Because of the rarity of pediatric gliosarcomas, these tumors are poorly characterized clinically and molecularly. 1,4 Neurofibromatosis type 1 (NF1) is a neurocutaneous syndrome defined by mutation of the NF1 gene, a well-known tumor suppressor of the RAS oncogene. Individuals with NF1 are known to be at a higher risk of developing gliomas including high-grade tumors 5 such as GBM; however, published reports of gliosarcoma in NF1 patients are limited to adult cases with only sparse molecular data.…”
mentioning
confidence: 99%
“…Only about 2% of childhood GBMs are gliosarcomas1 accounting for only 2 cases annually in the United States 2,3. Because of the rarity of pediatric gliosarcomas, these tumors are poorly characterized clinically and molecularly 1,4. Neurofibromatosis type 1 (NF1) is a neurocutaneous syndrome defined by mutation of the NF1 gene, a well-known tumor suppressor of the RAS oncogene.…”
mentioning
confidence: 99%